Calcium homeostasis and cone signaling are regulated by interactions between calcium stores and plasma membrane ion channels. - Tamas Szikra; Peter Barabas; Theodore M Bartoletti; Wei Huang; Abram Akopian; Wallace B Thoreson; David Krizaj (PLoS ONE, 2009)
Calcium is a messenger ion that controls all aspects of cone photoreceptor function, including synaptic release. The dynamic range of the cone output extends beyond the activation threshold for voltage-operated calcium entry, suggesting another calcium influx mechanism operates in cones hyperpolarized by light. We have used optical imaging and whole-cell voltage clamp to measure the contribution of store-operated Ca(2+) entry (SOCE) to Ca(2+) homeostasis and its role in regulation of neurotransmission at cone synapses. Mn(2+) quenching of Fura-2 revealed sustained divalent cation entry in hyperpolarized cones. Ca(2+) influx into cone inner segments was potentiated by hyperpolarization, facilitated by depletion of intracellular Ca(2+) stores, unaffected by pharmacological manipulation of voltage-operated or cyclic nucleotide-gated Ca(2+) channels and suppressed by lanthanides, 2-APB, MRS 1845 and SKF 96365. However, cation influx through store-operated channels crossed the threshold for activation of voltage-operated Ca(2+) entry in a subset of cones, indicating that the operating range of inner segment signals is set by interactions between store- and voltage-operated Ca(2+) channels. Exposure to MRS 1845 resulted in approximately 40% reduction of light-evoked postsynaptic currents in photopic horizontal cells without affecting the light responses or voltage-operated Ca(2+) currents in simultaneously recorded cones. The spatial pattern of store-operated calcium entry in cones matched immunolocalization of the store-operated sensor STIM1. These findings show that store-operated channels regulate spatial and temporal properties of Ca(2+) homeostasis in vertebrate cones and demonstrate their role in generation of sustained excitatory signals across the first retinal synapse.